Міжнародно-правова відповідальність за невиконання міжнародних зобов'язань з охорони морського середовища - Короткий, Тимур Робертович; Короткий, Тимур Робертович; Korotkij, Т. (My University, 2012)
The questions of international law responsibility of states for non-fulfi llment of international responsibilities on guard of marine environment are considered. The theoretical aspects of international law responsibility, its grounds and order of ealization are studied. Provisions of UNO Convention on a naval law 1982 about responsibility of states for non-fulfi llment of responsibilities on guard of marine environment are analysed.
Короткий Т. Р. Міжнародно-правова відповідальність за невиконання міжнародних зобов'язань з охорони морського середовища / Т. Р. Короткий // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 90-101.
Keywords: міжнародне морське право; міжнародні зобов’язання з охорони морського середовища; відповідальність держав за невиконання міжнародних зобов’язань з охорони морського середовища; международное морское право; международные обязательства по охране морской среды; ответственность государств за невыполнение международных обязательств по охране морской среды; international admiralty law; international obligations for the protection of the marine environment; State responsibility for failure to comply with international obligations for the protection of the marine environment